LSD-assisted psychotherapy for anxiety associated with a life-threatening disease: A qualitative study of acute and sustained subjective effects. (January 2015) - Gasser, Peter; Kirchner, Katharina; Passie, Torsten
Objective: A recently published study showed the safety and efficacy of LSD-assisted psychotherapy in patients with anxiety associated with life-threatening diseases. Participants of this study were included in a prospective follow-up. Method: 12 months after finishing LSD psychotherapy, 10 participants were tested for anxiety (STAI) and participated in a semi-structured interview. A Qualitative Content Analysis (QCA) was carried out on the interviews to elaborate about LSD effects and lasting psychological changes. Results: None of the participants reported lasting adverse reactions. The significant benefits as measured with the STAI were sustained over a 12-month period. In the QCA participants consistently reported insightful, cathartic and interpersonal experiences, accompanied by a reduction in anxiety (77.8%) and a rise in quality of life (66.7%). Evaluations of subjective experiences suggest facilitated access to emotions, confrontation of previously unknown anxieties, worries, resources and intense emotional peak experiences à la Maslow as major psychological working mechanisms. The experiences created led to a restructuring of the person's emotional trust, situational understanding, habits and world view. Conclusions: LSD administered in a medically supervised psychotherapeutic setting can be safe and generate lasting benefits in patients with a life-threatening disease. Explanatory models for the therapeutic effects of LSD warrant further study.